Assessing popularity of rabbits among children (Indian Journal of Animal Production and Management, 2025)
Animals have always been man’s companion. Among the favourites like dog and cat, rabbit also have a scope of being a good pet option. However, rabbits have fetched little attention compared to other species. Hence the present study was taken up to gauge the popularity of rabbits among children of different age groups. It was found that eagerness level towards approaching rabbits and higher level of excitement on seeing rabbits was more evident in children of ≥10 years. Overall, 97.67% children showed high level of liking towards rabbits. All the boys of all age groups (100%) showed liking towards rabbits, while a small proportion of girls (2.77%) belong to the age group of ≥10yrs did not show any liking towards rabbits. Out of all 6 breeds included in the study, New Zealand White breed was preferred by most of the children followed by Angora, Black Brown, Soviet Chinchilla, Grey Giant and Californian White. Leporiphobia was seen in 12.24% of boys and 27.01% of girls. Majority of children of all age groups wanted to take the rabbits home. Null hypothesis was rejected and it was concluded that children show liking and attraction towards rabbits and the most liked breed of rabbit was New Zealand White breed.
Keywords: Rabbit, New Zealand White rabbit, Preference, Pet, Leporiphobia